Constitutional Legislation as a Historical Situation of the Embodiment of Reason. on the Relation Between Democracy and Human Rights - Lohmann, Georg (Practica et Speculativa: Studies Offered to Professor Andrzej M. Kaniowski, 2022)
Based on three open questions, which Habermas poses at the end of his two-volume book “Also a History of Philosophy”, the national constitution-making of a people is reconstructed as an answer to the first question, following Julius Froebel. Already the elements of a public opinion formation answer the third question, in which the constitution- making can already establish the egalitarian universalism of the human rights, which then become constituted basic and human rights in the general will-making. However, the open questions and ambivalent solutions of the national constitutional formulations, such as the promotion of capitalist economy or political de-democratizations, make it clear that the answer to the second question in international human rights must remain open and require morally unbound efforts.